Tracing policy change: Intercurrent (de)politicisation and the decline of nationalisation in the 1970s. (May 2023) - Warner, Sam; Luke, Darcy
When faced with complex public policy challenges, policymakers grapple with a dilemma between assuming direct political control (politicisation) or creating 'distance' through arm's length, often market-orientated governance arrangements (depoliticisation). We contend that both processes co-exist and operate simultaneously though empirically speaking, little is known about how they interact over time to inform policy change. We compare how the Heath and Wilson-Callaghan governments responded to this 'recurrent dilemma' in the Nationalised Industries during the 1970s. Drawing on new archival material, our research reveals that a desire to retain political control was repeatedly supplemented by attempts to embed depoliticising, quasi-market disciplinary mechanisms. Our focus on the 'intercurrence' of politicisation and depoliticisation, understood as the simultaneous operation of older and newer governance arrangements, reveals the long, complex lineage of privatisation, adding nuance to accounts that present it simplistically as part of a paradigm shift in the 1980s.